Randomized double blind comparative study on efficacy and safety of oral oxaceprol 200 mg versus oral diclofenac 50 mg in patients with moderate osteoarthritis - Adamrafi, P. G. M.; Prayaga, Usha Kiran; Venkateswarlu, B. S. S. (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Osteoarthritis of knee is the most common form of arthritis globally, approximately 250 million people are suffering from osteoarthritis of the knee alone throughout the world. It is a chronic joint disease leading to cause cartilage degradation that involves synovial Inflammation, Subchondral bone remodelling, and Formation of osteophyte pathologically, which leads to cause pain, joint destruction and difficulty in walking. Aim of the current study was to compare the safety and efficacy of oxaceprol 200 mg versus diclofenac 50 mg in patients with moderate osteoarthritis and to determine cost-effectiveness between these two drugs Methods: this is a randomized controlled study, in our study total of 94 patients were screened, of which 85 patients met inclusion & exclusion criteria. In this, 78 members gave written informed consent, they were randomly assigned by double-blind fashion into two treatment groups (oxaceprol and diclofenac). Results were analyzed by applying paired and unpaired student t-test by using SPSS software Results: In our study, both oxaceprol and diclofenac were extremely significant in reducing joint pain and joint stiffness and improving physical activity, but when comparing with one another oxaceprol group showed better results in improving physical activity Conclusions: From our study, it is concluded that oxaceprol is equally efficacious as diclofenac in reducing knee pain, joint stiffness but more efficacious than diclofenac in improving physical activity of patients by enhancing bone remodelling.